Beban Perawatan dan Ketimpangan Gender: Studi Sosiologis tentang Kesejahteraan Sosial di Masyarakat Pedesaan - Syaifudin Suhri Kasim; Megawati Asrul Tawulo; Lutfiana Nur Azizah; Dian Puspita Rizki; Hasyim Abdillah (Jurnal Neo Societal, 2026)
This study aims to analyze the relationship between care burden and gender inequality in the construction of social welfare in rural communities. This study uses a qualitative approach with case study methods in rural communities, through in-depth interviews, participatory observations, and analysis of local social policy documents. The findings show that women bear a double burden: as the main responsible for domestic work and unpaid care, as well as as economic actors in supporting household incomes. This burden not only limits women's access to productive resources and social mobility, but also reproduces structural inequalities in the distribution of welfare. In addition, social protection policies tend to assume women as beneficiaries as well as managers of family welfare, without substantively reducing the burden of care they bear. This study concludes that care work is a key element of social welfare in rural areas, but it is mostly imposed on women. Women must carry out a dual role, namely taking care of the household while earning a living, so that their opportunities to develop are limited. This causes gender inequality to continue to occur. This research contributes to strengthening the sociological perspective of welfare by placing care work as a central arena in the analysis of gender inequality and social policy.